PROGRAM PENINGKATAN KESEJAHTERAAN MASYARAKAT dan PENGEMBANGAN POTENSI WILAYAH MELALUI USAHA DESA WISATA serta INDUSTRI KREATIF DI KECAMATAN IMOGIRI BANTUL - Prihatin Saraswati (Jurnal Socia Akademika, 2020)
ABSTRACT This research aims to illustrate the potential of Wukirsari Imogiri village area that can be developed into a tourism village business and creative industry to improve the welfare of the community. This research uses a qualitatively described approach in describing the natural potential, cultural potential and potential of the existing creative industry and analyzed using SWOT analysis In this research it appears that there is a very large strength of the potential of Wukirsari village which if developed into a tourism village business will be a destination that attracts tourists the potential of nature to describe a beautiful natural panorama with the situation of agricultural areas surrounded by hills on which there are tombs of mataram kings and the existence of natural cosmodivization in bird breeding is very wide in addition to the potential of creative industries that are the forerunners of the Industry Wedang uwuh , batik handicrafts with natural coloring, making leather puppets engan sungging tatah techniques and various handicrafts from bamboo. This potential is not owned by other regions so that if developed with modern tourism management will become a natural tourist destination, culture and creative industry. The weakness seen in this area is the relatively low level of public education because the level of the economy is also relatively low so to develop the potential is not yet maximal because most of the community does not have low awareness and participation. Opportunities in developing the potential is very large because of the uniqueness of its potential and the development of tourism villages into government programs so that many programs can be cooperated with other parties both government and private. The threat in the development of the program because the area, especially Bantul Regency, develops many coastal tourism areas that are geographically adjacent and the development of other tourism villages such as leather handicraft industry, culinary clay that has existed so that it becomes a competitor for the development of creative industries in the village wukirsari Imogiri Bantul